Caracterización de personajes icónicos de los barrios populares de Latacunga con base en los elemetos de la gráfica popular de la provincia de Cotopaxi. - Anchatuña Saquinga, Silvana Elizabeth (2019)
This investigation project has as objective, the realization of iconic graphic pieces of popular districts characters from Latacunga based on popular elements of Cotopaxi province. Through the use of mixed illustration technique (analogue and digital) an aesthetic composition of the popular graphic was obtained and the characterization of personages becoming an informative element with the purpose to generate a graphic product that helps to strengthen and spread in a graphic way the social aspects of the forgotten personalities belonging to Latacunga city neighborhoods. Through field research techniques such as interview, focus group, bibliographic sources, theoretical information and different research methodologies such as: Bruno Munari (1983) "How objects are born", Ramón Ortega (2014) "Methodology for illustration from the creative thought "and Guzmán Ramírez, Jesús (2016)" The methodology for the creation of personages from the concept design". Based on the methodologies, a workflow is shown that allows the correct execution of this project.